PEMBELAJARAN KONSEP PENGUKURAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN PENDEKATAN KONSTRUKTIVISME DI KELAS III DI SD NEGERI 1 SUKARAME BANDAR LAMPUNG - Djumroh, Djumroh (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The objective of this research is to investigate the incresing of students’ learning outcomes using constructivism approach at the third grade students of SD Negeri 1 Sukarame. This study is classroom action research. The participants come from the third grade students of SD Negeri 1 Sukarame Bandar Lampung. After doing a research, iit is found that constructivist approach can be planned in learning the concept of measurement in the classroom. This is evident from the findings that the plan that has been prepared can be performed well. The constructivist approach can be implemented in learning the concept of measurement in the third class. This is evident from the findings that the increased activity of students in learning, interaction of learners with learners, the rest of the teachers, as well as the interaction of learners with the environment to be increased.